An Intelligent Reconfiguration Approach Based on Fuzzy Partitioning in PV Arrays - Karakose, Mehmet; Baygin, Mehmet; Baygin, Nursena; Murat, Kagan; Akin, Erhan (Ieee, 2014)
The reconfiguration process in photovoltaic (PV) arrays is very important to obtain maximum power under partial shading conditions. Connection architecture of array for this process is changed according to status of non-uniform shadows. However, finding of best connection in big PV arrays is hard in real-time. In this paper, a new efficient and intelligent reconfiguration approach based on partitioning of array is proposed. The proposed approach is aimed to search best connection from possible connections in several small-sized array partitions obtained with decomposing according to location of shadows to carry out control task. Thus, search space of possible connections is considerably reduced for using in real time implementation of reconfiguration process in big size PV arrays. Efficiency, accuracy, and performance proposed reconfiguration approach has been verified for different size and shading conditions with comparative simulation results.
IEEE International Symposium on Innovations in Intelligent Systems and Applications (INISTA) -- JUN 23-25, 2014 -- Alberobello, ITALY
Keywords: partitioning; reconfiguration; PV arrays; time efficiency